The social factors of low birth weight in working area of sudiang health center makassar, 2019 - Samsinar Samsinar; Nurdiyanah Syarifuddin; Sukfitrianty Syahrir (CORE JOURNAL, 2020)
The cases of low birth weight are closely related to the problems of growth and development in infants. There are several factors that contribute to low birth weight. This study aimed to determine the social factors of low birth weight in working area of Sudiang Health Center, Biringkanaya, Makassar in 2019. This was observational study with case control design. The comparison of case and control was 1:1. About 28 cases were selected with purposive sampling technique. Data were analysed with chi square test and odds ratio calculation. The results showed that social demographic factors such as knowledge (OR=4.50), attitudes (OR=1.56), behaviours (OR=6.60), health status (OR=2.06), and family support (OR=2.81) influenced the low birth weight in infants. Activities pattern (OR=0.51) and cultures (OR=0.39) identified as protective determinants of low birth weight. The awareness of the society on the importance of health and the risk of low birth weight was needed to be increased by education given by the health officers by using a number of different methods.